Desenvolvimento de um biossensor a base de hemina para análise de amodiaquina em leite materno - Valente, Cristiane Oliveira (2010)
This research had as main objective to develop an electroanalytical procedure for the determination of amodiaquine in human milk, using a carbon paste electrode modified with hemin, hemoglobin functional group responsible for transporting oxygen. The amodiaquine (a derivative 4-aminoquinoquinolínico) is a drug used to treat malaria with anti-inflammatory and antipyretic properties. The characterization and preparation of carbon paste electrode modified with hemin was investigated. The electrochemical behavior of modified electrode was explored using differential pulse voltammetry. The best voltammetric response was obtained for the composition of carbon paste 10% hemin solution in Britton-Robson buffer pH 7.0. To study the electrochemical behavior of amodiaquine was used the technique of cyclic voltammetry, which presented in a neutral medium oxidation process at 0.054 V vs. Ag / AgCl at a rate of 20 mV s-1. The voltammetric techniques used to develop the methodology where the differential pulse voltammetry and square wave voltammetry. In this study the optimized conditions were: pH 7, scan rate = 40 mV s-1, amplitude = 200 mV and frequency = 150 Hz, where the parameters indicated the square wave voltammetry as the best technique for determining the voltammetric amodiaquine has a minor detection limit. The limits of detection and quantification were obtained in the determination of 8.7 x 10-7 mol L-1 and 2.9 x 10-6 mol L-1, respectively. After optimization of all relevant parameters, the analytical method developed was successfully applied in samples of breast milk. The concentration of amodiaquine obtained was 1.7 x 10-5 mol L-1. The method was efficient and reproducible in the determination of amodiaquine present in breast milk, there is no need any pretreatment of the sample.